Analysis of The Effectiveness of Gopay Advertising "100x Free Transfers per Month" on Youtube using The Aisas Method - Amartiwi, Yasinta; Krisdayanti, Nyoman Anggi; Wibasuri, Anggalia; Sahondra, Vatsiniaina Tatamo (Prosiding International conference on Information Technology and Business (ICITB), 2023)
PT. Gojek Indonesia is an application providing company that provides transportation, payment, logistics and other services. Of the several services offered, Go-jek provides an electronic wallet (e-wallet) called Go-pay. In 2023, E-wallet platform the most widely uses Gopay, with a user proportion of 71%. PT Gojek Indonesia's achievement with the most superior users is the impact of promotions through advertising carried out by PT. Gojek Indonesia. Advertisements on Gopay use YouTube social media as promotional media. The phenomenon that occurred, based on data, was that the number of viewers on the Gopay advertisement "Free Transfer 100x" increased within two months. This research is entitled "Analysis of the Effectiveness of 100x Free Transfer Gopay Ads on YouTube using the AISAS Method" using the Quantitative Descriptive method and sampling in this research using a nonprobability sampling method with purposive sampling technique. The sampling taken was 100 respondents which was calculated using the Slovin formula. The results of the AISAS (Attention, Interest, Search, Action, Share) method analysis of the effectiveness of Gopay advertising on YouTube with an average Attention score of 68.1% which is categorized as good, Interest of 62.9% which is categorized as good, Share of 67% is categorized as good, Action is 66.7% which is categorized as good, Share is 63.4 which is categorized as good.Keywords—Social Media, Gojek, AISAS Model